PfHMGB2 has a role in malaria parasite mosquito infection - Kumar, Sudhir; Kappe, Stefan H. I. (Frontiers in Cellular and Infection Microbiology, 2022)
Differentiation of asexually replicating parasites into gametocytes is critical for successful completion of the sexual phase of the malaria parasite life cycle. Gametes generated from gametocytes fuse to form a zygote which differentiates into ookinetes and oocysts. The sporozoites are formed inside oocysts which migrate to the salivary glands for next cycle of human infection. These morphologically and functionally distinct stages require stage-specific gene expression via specific transcriptional regulators. The capacity of high mobility group box (HMGB) proteins to interact with DNA in a sequence independent manner enables them to regulate higher order chromosome organization and regulation of gene expression. Plasmodium falciparum HMGB2 (PfHMGB2) shows a typical L- shaped predicted structure which is similar to mammalian HMG box proteins and shows very high protein sequence similarity to PyHMGB2 and PbHMGB2. Functional characterization of PfHMGB2 by gene deletion (Pfhmgb2¯) showed that knockout parasites develop normally as asexual stages and undergo gametocytogenesis. Transmission experiments revealed that Pfhmgb2¯ can infect mosquitoes and develop as oocyst stages. However, transmission was reduced compared to wild type (WT) parasites and as a consequence, the salivary gland sporozoites were reduced in number. In summary, we demonstrate that PfHMGB2 has no role in asexual growth and a modest role in sexual phase development and parasite transmission to the mosquito.